Avaliação da influência dos mastócitos uterinos e de células de glicogênio na zona juncional de placentas de camundongos BALB/c e C57BL/6 gestantes em modelo de infecção congênita por Toxoplasma gondii - Sousa, Romulo Oliveira (2018)
The spiral arteries remodeling is the hallmark of gestation to successful nutrition from mother to fetus and uterine mast cells contribute to this remodeling. Several factors may contribute to a restriction of this energy supply, including congenital diseases such as toxoplasmosis. Toxoplasma gondii infection induces a Th1 response profile that is associated with detrimental results from gestation. To investigate the influence of congenital toxoplasmosis on the maternal fetal interface, C57BL/6 and BALB/c mice were orally infected with 5 cysts of the ME-49 strain on 1° or 14° day of gestation and sacrificed at 8° or 19° days after infection, respectively. No parasites were found in uterus/placenta. Regardless to infection time and there was no IgA production in the analyzed samples of serum and uterine/placental homogenate. Infection in non-pregnant C57BL/6 females caused a migration increase of mast cells to the uterus whereas gestation decreases the migration. In addition, C57BL/6 mice had high systemic levels of TNF and IL-6 compared to pregnant and non-pregnant BALB/c mice. In addition, in the uterus/placenta of the C57BL/6 females infection increased the amount of glycogen cells at end gestation. In conclusion, we found that infection with T. gondii during early gestation leads to increase in systemic and local TNF and IL-6 levels at maternal fetal interface in C57BL/6 mice. These proinflammatory cytokines induce excessive recruitment of mast cells into the uterus, which results in damage to the embryo and cause hemorrhage, necrosis and reabsorption. The increase of glycogen cells in the placenta of C57BL/6 mice seems to contribute to the normal development of fetuses of this strain of mice.